Hyperglycemia-induced involuntary movements : what you should know - Mohd Fazrul M,; Tan, Toh Leong (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Hemichorea-hemiballismus (HC-HB) is a movement disorder characterized by involuntary movements involving limbs on one side of the body. Many etiological factors were identified and these included stroke, infection, and neoplasm. However, acute hyperglycemia-induced HC-HB is less well known. We present two cases of non-ketotic hyperglycemia-induced HC-HB. The cases depicted here Illustrate that HC-HB can be the sole presentation from among a variety of neurological manifestations of poorly controlled diabetes which can be easily reversed when hyperglycemia is corrected.